Clinicopathological features and outcome in elderly patients with idiopathic membranous nephropathy - Jinxiu Liang; Wenke Hao; Fangxiao Xia; Zhi Zhao; Yanhua Wu; Feng Yu; Wenxue Hu; Xiaowu Fang; Wei Liu (Renal Failure)
Background Idiopathic membranous nephropathy (IMN) is the leading cause of nephrotic syndrome in the elderly. The treatment of idiopathic membranous nephropathy is quite challenging due to the particularity of elderly patients. This study intends to investigate the clinicopathological characteristics and initial therapeutic effect of idiopathic membranous nephropathy among elderly patients.Methods A retrospective study of 67 elderly patients (58.2% male, median age 69.0 years, range, 65–83 years) with biopsy-proven membranous nephropathy was conducted at Guangdong Provincial People’s Hospital from 2016 to 2020. Data on clinicopathological characteristics and initial therapeutic effects were analyzed.Results Of the 67 patients, the mean eGFR of overall patients was 66.49 mL/min/1.73m2 while the median urine protein-to-creatinine ratio (uPCR) and urine albumin-to-creatinine ratio (uACR) was 5676.73 mg/g and 2951.56 mg/g, respectively. Pathological data revealed that the membranous Churg’s stage II was the most frequent (71.64%). Moreover, glomerular PLA2R antigen fluorescence intensity of (+) and IgG4 antigen fluorescence intensity of (++) were detected in 63.6% and 86.4% of all patients, respectively. Overall, 44 patients, accounting for 65.7%, achieved remission including complete remission and partial remission within 1 year after renal biopsy. Compared with a non-remission group, the levels of uPCR (6274.6 vs. 3235.6 mg/g, p = 0.007) and uACR (3433.6 vs. 1773.2 mg/g, p = 0.017) were significantly higher in remission group. The proportion of immunosuppressive therapy in the remission group was also higher (86.4% vs. 30.4%, p < 0.01). Compared with conservative treatment, patients with combined treatment with glucocorticoid and cyclophosphamide (CTX) or glucocorticoid and calcineurin inhibitor (CNIs) achieved higher remission rate (glucocorticoid plus cyclophosphamide vs. conservative treatment, 84.6% vs. 27.3%, p = 0.001; glucocorticoid plus calcineurin inhibitor vs. conservative treatment, 88.0% vs. 27.3%, p < 0.001). Further analysis showed that compared with patients who underwent conservative treatment, the proportion of males, the levels of uPCR, uACR, BUN, Scr, CysC and PLA2R antigen-positive staining rate in kidney biopsy were higher in those who underwent combined treatment with glucocorticoid and CTX, while the levels of eGFR, TP and ALB were lower (p < 0.05). In addition, patients who received combined treatment with glucocorticoid and CNIs had higher levels of uPCR, uACR, TC and lower levels of TP, ALB than those who received conservative treatment (p < 0.05). Moreover, there were no statistically significant differences in the 1-year progression rate in eGFR between the immunosuppressive treatment group and conservative treatment group (3.3 vs. 0.2 ml/min/1.73m2, p = 0.852).Conclusions Most elderly patients diagnosed with IMN had multiple comorbidities, and the membranous Churg’s stage II was most common. The glomerular PLA2R and IgG4 antigen deposition were frequently detected accompanied by glomerulosclerosis and severe tubulointerstitial injury. For high-risk elderly patients with severe proteinuria, early initial immunosuppressive therapy could achieve a higher urinary protein remission rate. Therefore, it is crucial for clinicians to balance the risks and benefits of immunosuppressive therapy based on clinical and pathological characteristics and develop individualized treatment regimens for elderly patients with IMN.